'There is nothing there': Deindustrialization and loss in a coastal town. (April 2022) - Telford, Luke
Based on 52 qualitative interviews with working-class individuals, this paper explores the social and economic decline of a coastal locale referred to as High Town in Teesside in the North East of England. First, the paper outlines how the locality expanded as a popular seaside resort under capitalism's post-war period. It then assesses how the seaside existed together with industrial work, offering stable employment opportunities, economic security and a sense of community. Next, the article documents the shift to neoliberalism in the 1980s, specifically the decline of High Town's seaside resort, the deindustrialization process and therefore the 2015 closure of High Town's steelworks. It explicates how this exacerbated the locale's economic decline through the loss of industrial work's 'job for life', its diminishing popularity as a coastal area and the further deterioration of the town centre. The paper concludes by suggesting that High Town has lost its raison d'être under neoliberalism and faces difficulties in revival.